The Newly Developed Elderly Nutrient-Rich Food Score Is a Useful Tool to Assess Nutrient Density in European Older Adults - Berendsen, Agnes A. M.; Kramer, Charlotte S.; de Groot, Lisette C. P. G. M. (Frontiers in Nutrition, 2019)
Objective: To develop a nutrient rich food score that captures dietary reference values for older adults and to validate this against a diet index that was specifically designed to assess adherence to dietary guidelines for the ageing population. Design: A cross-sectional study within the Dutch National Food Consumption Survey (DNFCS, n=735 men and women aged 70-94 years, enrolled between October 2010 and February 2012) and within the NU-AGE study (n=250 men and women aged 65-79 years, enrolled between April 2012 and March 2013). Dietary intake was assessed by means of two non-consecutive dietary record assisted 24-hour recalls and 7–day food records, respectively. Structured questionnaires collected data on lifestyle and socio-economic information. Anthropometrics were measured by trained dieticians or research assistants. We evaluated Elderly NRF (E-NRF) scores against the NU-AGE index, a measure of adherence to European dietary guidelines for the ageing population. The E-NRF scores were composed of nutrients that: 1) have been shown to be of inadequate intake in the ageing population (>20%), 2) were defined as nutrients of public health relevance, and 3) were associated with relevant health outcomes. Results: The E-NRF score that best predicted the NU-AGE index included seven nutrients to encourage (protein, dietary fiber, folate, vitamin D, calcium, magnesium, potassium), and three nutrients to limit (saturated fat, sodium and mono- and disaccharides) on a 100-kcal basis, the E-NRF7.3 (model R2 0.27 in DNFCS and 0.41 in NU-AGE). Food groups contributing the most to the individual E-NRF7.3 scores were vegetables, bread, potatoes and milk and milk products. Conclusion: The results suggest that the E-NRF7.3 is a useful tool for assessing nutrient density of diets within the ageing population. No index has previously been developed with the aim of evaluating nutrient density of diets and foods specifically capturing dietary reference values for older adults.